QoS Analysis of Wireless Sensor Networks for Temperature and Humidity Monitoring and Control of Soybean Seed Storage Based IOT Using NodeMCU - Sindung HW Sasono (Politeknik Negeri Semarang, 2017)
Based on data from Central Bureau of Statistics in 2016 - 2020 soybean production deficit, the main factor is the decline in the quality of soybean seeds temperature and humidity sensitive. And so we need a system of monitoring and control of temperature and humidity container store soya beans. Wireless sensor network wireless technology that consists of a collection of sensor nodes distributed on a given area can support the communication between the sensor nodes using the system and sensor NodeMCU DHT11. This research was to analyze the WSN QoS monitoring system and temperature and humidity control soybean seed store container-based IOT using NodeMCU clients and coordinators are connected to an access point for sending data to the server in realtime. Tests carried out by putting the sensor node at 3 points with a distance variation of the coordinator and a data packet transmission interval. The test results obtained using a star topology indoor NLOS conditions optimal distance sensor node 3 which is 4 meters and the delivery interval 40s with packet loss value of 0-20%, delay 1.154 - 5,92s, jitter 0.241 to 7.57 ms, and throughput 66.32 bits / s. WSN protocol IOT uses MQTT NodeMCU and goes well with a low throughput value is 529.81 bps to 544.85 bps can still generate a delay kualiatas 200.33 to 270.83 ms and packet loss from 0 to 1.284% which is good. 92s, jitter 0.241 to 7.57 ms, and the throughput of 66.32 bits / s. WSN protocol IOT uses MQTT NodeMCU and goes well with a low throughput value is 529.81 bps to 544.85 bps can still generate a delay kualiatas 200.33 to 270.83 ms and packet loss from 0 to 1.284% which is good. 92s, jitter 0.241 to 7.57 ms, and the throughput of 66.32 bits / s. WSN protocol IOT uses MQTT NodeMCU and goes well with a low throughput value is 529.81 bps to 544.85 bps can still generate a delay kualiatas 200.33 to 270.83 ms and packet loss from 0 to 1.284% which is good.